Sanitasi Dan Kepadatan Penduduk Sebagai Dinamika Kemiskinan Kota Studi Kasus Provinsi Jawa Barat - Syifa Putri Nur Azizah; Liliani Sumarni Pratiwi; Ima Amaliah; Freska Fitriyana (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2022)
The purpose of this study was to determine the effect of population density and sanitation on poverty in urban areas of West Java Province. The data used in this study are secondary data and primary data sourced from the Central Statistics Agency (BPS) and field observations consisting of the percentage of poor people, population density and proper sanitation in urban areas of West Java Province. The number of observations in this study was 45 consisting of data from 9 cities in West Java Province from 2016 to 2020. The analysis technique in this study uses panel data with the Random Effect Model. The results of this study indicate that population density and sanitation partially have a negative and significant effect on poverty in urban areas of West Java Province. Then simultaneously population density and sanitation have a significant effect on poverty in urban areas of West Java Province.